2020
DOI: 10.29252/rbmb.9.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Relative Expression of SOX2 and OCT4 in Oral Squamous Cell Carcinoma and Oral Epithelial Dysplasia

Abstract: Background: Over 90% of oral cancers including oral squamous cell carcinoma (OSCC), originate from the oral cavity epithelium. Early detection for this lesion is as important. Evaluating cancer stem cell markers can improve the accuracy of early diagnosis, and be used as an OSCC prognostic indicator. We aimed to evaluate SOX2 and OCT4 gene expression among different grades of OSCC and oral epithelial dysplasia (OED) lesions. Methods: Sixty samples that contains 45 OSCC and 15 OED samples were retrieved from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Concordantly, analogous observation was obtained from the analysis of a series of 348 tumors located in oropharynx, hypopharynx and larynx [81], while quite remarkably, different OCT4 antibodies were employed in both studies. Ghazi et al [82] found that SOX2 expression did not correlate with OCT4 expression in OSCC. Additionally, Vijayakumar et al [83] studied 20 cases of OSCC and 20 cases of oral epithelial dysplasia (OED), and found that SOX2 expression was higher in OSCC than in OED; most cases predominantly showed high SOX2 expression accompanied by negative OCT4 expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Concordantly, analogous observation was obtained from the analysis of a series of 348 tumors located in oropharynx, hypopharynx and larynx [81], while quite remarkably, different OCT4 antibodies were employed in both studies. Ghazi et al [82] found that SOX2 expression did not correlate with OCT4 expression in OSCC. Additionally, Vijayakumar et al [83] studied 20 cases of OSCC and 20 cases of oral epithelial dysplasia (OED), and found that SOX2 expression was higher in OSCC than in OED; most cases predominantly showed high SOX2 expression accompanied by negative OCT4 expression.…”
Section: Discussionmentioning
confidence: 98%
“…OCT4 and SOX2 have been reported to play different roles in CSC biology. In the absence of OCT4 expression, neoplasms could not be initiated from normal tissues, but without SOX2 expression, the neoplastic cells could not be self-renewed to maintain tumor growth [82]. Nestin is considered a CSC marker in epithelial neoplasms and has been shown to play key roles in differentiation, proliferation, migration, invasion, metastasis and survival of malignant neoplastic cells through regulation of the cytoskeleton and progenitor cells [83].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this parameter may be a better predictive biomarker for MCT oncogenesis than the others. Ultimately, we recommend conducting a further study to verify the interaction of Oct-4 and Sox-2 in MCT crossbred dogs because the co-expression frequently enhances the aggressiveness and progression of some human neoplasms [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin functions through the MT1 receptor dependent extracellular signalregulated protein kinase (ERK)1/2 pathway (14). The increased expression of SOX2 is correlated to oral mucosal carcinogenesis which is speculated to be important marker in cancer stemness (15). SOX2 expression is upregulated in immature Schwann cells after PNI event (16).…”
Section: Introductionmentioning
confidence: 99%